The Pycnogonids (Arthropoda, Pycnogonida) of Torrevaldaliga (Tyrrhenian Sea), Italy, with data on Endeis biseriata, new record for the Mediterranean Sea. Issue 1 (1st January 2021) - Colasanto, E.; Galli, L.
Abstract: New data about the Mediterranean pycnogonids are given. For this contribution, we analysed 315 samples that until now had remained unidentified, collected in 1979–1980 in the Tyrrhenian Sea close to Torrevaldaliga, Italy. We found six species: Ammothella appendiculata, Anoplodactylus californicus, Endeis biseriata, Endeis spinosa, Nymphon gracile and Tanystylum conirostre . Two of them are the subject of taxonomical and faunal remarks: morphological features of Anoplodactylus californicus specimens are reported and discussed, and the first record of Endeis biseriata for the Mediterranean Sea is reported.